Oviposition Behaviour and Genetic Relatedness of Scirpophaga incertulas Populations from Northwestern Sarawak - Nur Najwa, Hamsein (Universiti Malaysia Sarawak (UNIMAS), 2021)
The rice yellow stem borer, Scirpophaga incertulas (Walker) is an important pest of rice in Sarawak, Malaysian Borneo. For a better management of this pest, it is crucial to understand its biology and also other aspects such as the oviposition behaviour and the genetic structure which is unknown. The observation on the life cycle of S. incertulas was carried out under laboratory condition. The incubation period ranged between 7–9 days. The larval duration completed in 38–42 days. The pupal duration ranged 7–10 days. The female moths longevity was longer than the male moths with an average 4.30 ± 0.90 and 3.70 ± 0.50 days respectively. In this study, rearing of S. incertulas under laboratory condition seems to be not feasible. Mortality was the highest at larval stages hence resulted in low adult emergence. For the study on S. incertulas oviposition behaviour, several aspects of its behaviour on Sarawak rice landraces were observed in a net house experiment. A total of 180 females of S. incertulas were given access to six different rice landraces at three plant ages. The results indicated that rice plants at four-month old were strongly preferred for oviposition regardless of landraces. This is probably because of the height of the older plants as compared to the younger plants. Plants with high stature is easier to be identified by flying moths, making it preferable for the moths to rest and oviposit. The vertical distribution of egg masses on plant were varied. Oviposition on leaf surfaces showed a clear preference on the abaxial leaf surface. To analyze the genetic relatedness of S. incertulas populations, four ISSR and primers and two RAPD primers were used. The combined ISSR and RAPD DNA fingerprint had 78 reliable bands with 48 polymorphic bands. The analysis of pooled ISSR-RAPD showed S. incertulas population from Kuching and Samarahan were highly related with the index 0.72. The genetic diversity among S. incertulas populations estimated were comparable and the AMOVA analysis showed higher genetic variation within population. Higher genetic variation within population may suggest the presence of different biotypes in each population. The present study is the first attempt of assessing the genetic relatedness of S. incertulas populations from northwestern Sarawak. In conclusion, the life cycle duration of S. incertulas reared under laboratory condition was estimated with an average 60 days. The adult females preferred four-month old plant for oviposition as compared to younger plants. The populations of S. incertulas from northwestern Sarawak require further validation by adding more markers to reveal the genetic diversity.